Rent seeking in sequential group contests - Oliver Gürtler (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
In this paper, a group contest is analyzed, where the groups are allowed to determine their sharing rules either sequentially or simultaneously. It is found that in case the more numerous group determines its sharing rule prior to the smaller group, rent dissipation in the group contest is higher than in an individual contest. However, if the order of moves is endogenized, the smaller group will always act prior to the bigger group. Competition between the groups is in this way weakened and the groups are able to save on expenditures.
urn:nbn:de:bvb:19-epub-13501-2
Keywords: D72; 330; Group contest; rent seeking; sequential choices; sharing rule